The Protective Effect of Omeg-3 Against Carbimazole Induced Hepatotoxicity in Rats - Hussein Naser, Iman; Fawzi Ibrahim, Wafaa; Jabbar, Shaima; Hasim Al. Mosawi, Fatin (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Background: The majority of medicines can predispose liver injuries when given in overdoses or with long time such as Carbimazole which is used for treatment of thyrotoxicosis. These adverse effects could be minimized by co-administer an antioxidant agents such as Omega-3 fatty acids which can reduce hepatic cell damages and improve patient outcomes. Objective: The aim of this study is to evaluate the protective effect of Omega-3 in reducing hepatic damage by chemicals and drugs. Method: This study was conducted in thirty constitutive days, the animals were divided in equally numbered four groups. Control group, Carbimazole group, Omega-3 group, and Carbimazole and Omega-3 group. After the final treatment, blood was withdrawn from each animal for biochemical tests and then killed and the livers were isolated for histological studies. Result: The result of our study indicate that Omega-3 possess potential antioxidant effect that protect body organs from oxidative stress injuries. Red blood cells return to normal value hepatic enzyme ALP was reduced significantly in the protective group (p=0.007), other enzymes were not clearly reduced by Omega-3 supplement. Histological study show that Carbimazole group show a great hepatic deterioration such as distortion of liver architecture and necrosis area, while animal group treated with Carbimazole and Omega-3 represent a hepatic tissue with an appearance like a normal tissue. Conclusion: The findings of this study suggest that the basic mechanisms of the hepatoprotective effects of fish oil involve inhibition of oxidative stress, enhancement of cellular antioxidant defenses, and stabilization of cell membranes.